Immunobiotic feed developed with Lactobacillus delbrueckii subsp. delbrueckii TUA4408L and the soymilk by-product okara improves health and growth performance in pigs - Suda, Yoshihito (2021)
Lactobacillus delbrueckii subsp. delbrueckii TUA4408L is able to differentially modulate the innate immune response of porcine intestinal epithelial cells triggered by TLR4 activation. This strain also has a remarkable ability to grow on plant substrates. These two immunological and biotechnological characteristics prompted us to evaluate whether the soymilk by-product okara fermented with the TUA4408L strain can serve as an immunobiotic feed with the ability to beneficially modulate the intestinal immunity of piglets after weaning to improve their productivity. Our in vivo studies demonstrated that the administration of immunobiotic TUA4408L-fermented okara feed significantly increased piglet growth performance and meat quality. These positive effects were associated with the ability of the TUA4408L-fermented okara feed to beneficially modulate both intestinal microbiota and immunity in pigs. The immunobiotic feed improved the abundance of the beneficial bacteria Lactobacillus and Lactococcus in the gut of pigs, reduced blood markers of inflammation, and differentially regulated the expression of inflammatory and regulatory cytokines in the intestinal mucosa. These findings indicate that the immunobiotic TUA4408L-fermented okara feed could be an economical and environmentally friendly option to improve the growth performance and immune health of pigs.